Viral meningitis in Sub-Saharan Africa: trends in prevalence, etiologies, and diagnostic approaches - Alene Geteneh; Mulugeta Kiros; Ephrem Tamrat; Aragaw Tesfaye; Yalewayker Gashaw; Sirak Biset; Melese Abate Reta (Virology Journal)
Abstract Viral meningitis is a significant yet often underreported public health concern in Sub-Saharan Africa (SSA), where diagnostic limitations and surveillance gaps hinder accurate case detection. This systematic review examines epidemiological trends, etiologies, and laboratory diagnostic approaches to viral meningitis across SSA from 1987 to 2024. This data reveal that the prevalence of viral meningitis has shown an overall increasing trend, with a considerable year-to-year variability influenced by seasonal outbreaks, improved diagnostic methods, and enhanced surveillance efforts. Human enteroviruses (HEVs) were the most frequently identified causative agents, accounting for 1,164 confirmed cases, followed by the herpesvirus family, including Epstein-Barr virus (EBV) and cytomegalovirus (CMV). Other detected viral pathogens include mumps virus, adenoviruses, coxsackievirus, and arboviruses such as dengue virus. The shift from traditional viral cultures to polymerase chain reaction (PCR) and multiplex PCR has significantly improved the case detection. Despite these advancements, substantial gaps remain in diagnostic accessibility, surveillance systems, and less research focus on viral meningitis in SSA. Addressing these challenges through improved surveillance, enhanced diagnostic capacity, and targeted public health strategies is crucial for mitigating the burden of viral meningitis in the region.